2009
DOI: 10.1007/s11295-009-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of forest fragmentation in high-density Araucaria angustifolia populations in Southern Brazil

Abstract: Araucaria angustifolia is an endangered tropical/ subtropical coniferous of great interest for conservation due its economical, ecological, and social value. Only 3% of original Araucaria forests remain, which are generally confined to small forest fragments. Forest fragmentation can have serious consequences on genetic process in tree population, affecting long-term fitness and adaptability. To investigate the effects of forest fragmentation on genetic diversity and the structure of A. angustifolia population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
2
18
1
2
Order By: Relevance
“…Among the individuals sampled, we found a high heterozygote proportion, and many alleles were only in heterozygotes. The mean number of alleles was lower than that usually observed in population analysis with SSR markers (Collevatti et al, 2001;Bittencourt and Sebbenn, 2009;Bizoux et al, 2009). Observed and expected heterozygosities were similar between subpopulations.…”
Section: Resultscontrasting
confidence: 67%
“…Among the individuals sampled, we found a high heterozygote proportion, and many alleles were only in heterozygotes. The mean number of alleles was lower than that usually observed in population analysis with SSR markers (Collevatti et al, 2001;Bittencourt and Sebbenn, 2009;Bizoux et al, 2009). Observed and expected heterozygosities were similar between subpopulations.…”
Section: Resultscontrasting
confidence: 67%
“…These data lead us to propose that this species suffers from genetic inbreeding depression. Bittencourt and Sebbenn (2009) conducted a study using molecular markers to compare populations of Araucaria angustifolia in isolated fragments and large conservation areas. They observed that the isolated populations had fewer alleles than the populations from large conservation areas; this leads us to conclude that the isolated populations of A. angustifolia suffered from genetic depression.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have cited forest fragmentation as perhaps the most significant negative impact humans have on the environment because it reduces forest area, destroys habitat, and isolates populations (Green, 1994;Turner, 1996;Laurance et al, 2002;Armbrecht and Perfecto, 2003). The isolation caused by fragmentation has ecological and genetic implications, such as loss of habitat heterogeneity and loss of genetic variability (Bierregaard Jr. et al, 1992;Santos and Kinoshita, 2003;Rodríguez-Cabala et al, 2007;Bittencourt and Sebbenn, 2009). Fragmentation can affect the ability of populations to adapt to environmental changes and could compromise the future of the species (Barret et al, 1983;Noss, 1987;Kapos, 1989;Heldrick and Miller, 1992;Ellstrand and Elam, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…One possible approach to study of the impact of forest fragmentation on the genetic diversity of tree species is to compare the genetic diversity and structure between predisturbance adult populations and postdisturbance generations cohorts [10]. Such comparisons can reveal whether significant, potentially deleterious genetic changes are occurring in the present generation (e.g., [10][11][12][13] [14]. Machilus thunbergii Sieb.…”
Section: Introductionmentioning
confidence: 99%